(untitled) (East West Medical College Journal, 2026)
Background: Health promotion is one of the key determinants and strategies for individuals to promote and maintain good health. Therefore, this study aims to investigate health promoting lifestyles among college students and explore factors related to various health behaviors. Methods: This descriptive cross-sectional study was conducted among 175 respondents selected by using simple random sampling method from college students at Uttara High School & College, Uttara, Dhaka, Bangladesh. Relevant data were collected through face-to-face interview with the help of semi-structured questionnaire. Results: Present study showed that, the average age of the participants was 17.63±.77 years which was ranged from 16 to 19 years. Regarding health promoting lifestyle study revealed that more than (50.9%) of the respondents had good health promoting lifestyles . Participants revealed higher percentage of good health promoting lifestyle among female than male. Moreover, participants whose income was 30000 thousand or more revealed good percentage of health promoting lifestyle than less income. Conclusion: To promote health, life style factors and its modification play an important role. The study exhibited that, more than half participants had good health promoting life styles. Improving a health promoting lifestyles to achieve a desire goal requires a holistic approach that includes physical, mental and social well-being. EWMCJ Vol. 14, No. 1, January 2026: 21-25